Frequency and Risk Factors of Advanced Neoplasia in Korean Inflammatory Bowel Disease Patients with Low-grade Dysplasia - Kyeong Ok Kim; Dong Hyun Kim; Soo-Kyung Park; Division of Gastroenterology, Department of Internal Medicine and Inflammatory Bowel Disease Center, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, Seoul; Chang Kyun Lee; IBD Research Group of the Korean Association for the Study of Intestinal Diseases (KASID) (The Korean Journal of Gastroenterology)
Background/Aims: Studies on the clinical outcomes after detecting low-grade dysplasia (LGD) in patients with inflammatory bowel disease (IBD) are insufficient. This study evaluated the clinical features, frequency, and risk factors for advanced neoplasia in patients with IBD after an LGD diagnosis. Methods: The medical records of 166 patients with IBD from six university hospitals in Korea from 2010 to 2019 were reviewed retrospectively. LGD was diagnosed in all patients during surveillance. The frequency and risk factors for advanced neoplasia were evaluated, and the clinical features of patients with and without advanced neoplasia were compared. Results: Advanced neoplasia developed in 12 patients (six with large LGD, three with tubulovillous adenoma, and three with high-grade dysplasia), and all cases developed from UC. Patients with advanced neoplasia had significantly higher Mayo scores, and colitis-associated dysplasia was more common than sporadic lesions (83.3% vs. 29.9%; p<0.001). Multivariate analysis showed that colitis-associated LGD significantly increased the risk of developing advanced neoplasia (odds ratio [OR], 10.516; 95% confidence interval [CI], 2.064–53.577). Among patients with colitis-associated lesions, a significant risk factor for advanced neoplasia was a prior history of LGD (OR, 9.429; 95% CI, 1.330–66.863). Conclusions: Advanced neoplasia developed in 7.2% of patients with IBD and LGD. Most advanced neoplasms developed from colitis-associated lesions, and the risk was higher in patients with a history of LGD before index colonoscopy.